My Grandfather's Workshop - Meola, Louis J. (Tufts Archival Research Center, 2019)
After the death of my grandfather, I became aware of my internal conversation about the space he worked and lived in. His entire workshop, containing tools and unfinished projects, was left without a purpose. I’m drawn to the present emptiness of his workshop and all that remains. The act of creating my work from his space gives me the freedom to have a dialogue with the memory of my grandfather and his basement workshop. These items help revive the person I called grandfather; as both a person and the objects he surrounded himself in. His workshop enables me to memorialize objects that played integral roles in his day to day upkeep of his house. The repetitious process of printmaking provides an outlook on labor that is acknowledged through both the printing and created objects. The items chosen range from being highly representational to abstracted.